Being there : fieldwork in anthropology - Watson, C. W. (Anthropology, culture, and society., 1999)
"The nature of anthropological fieldwork changes from generation to generation, reflecting current personal, moral and political issues. This collection addresses the central position of fieldwork in modern social anthropology, examining previous works on the subject and locating a discussion of the nature of fieldwork within the context of current theoretical debates. Central to this analysis are the personal accounts of six anthropologists, all trained in the tradition of social anthropology and working in a variety of different social, economic and environmental settings - Italy, the Himalayas, Northern England, Bangladesh and Indonesia. Each example is a discussion of the close relationship which anthropologists establish with friends and informants in the field. Collectively they describe the varying ways in which that closeness affects the nature of the anthropologists' observation, as well as an understanding of themselves and their discipline."--Book description